2016
DOI: 10.1186/s12889-016-3691-8
|View full text |Cite
|
Sign up to set email alerts
|

A web-based group course intervention for 15-25-year-olds whose parents have substance use problems or mental illness: study protocol for a randomized controlled trial

Abstract: BackgroundDepending on the definitions used, between 5 and 20 % of all Swedish children grow up with at least one parent suffering from alcohol problems, while 6 % have at least one parent who has received inpatient psychiatric care, conditions that may affect the children negatively. Nine out of ten Swedish municipalities therefore provide support resources, but less than 2 % of these children are reached by such support. Delivering intervention programs via the Internet is a promising strategy. However, web-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The rapid development and uptake of new digital media presents significant potential for influencing health behaviours via health education, social marketing and health promotion interventions. New digital media have already been used in a range of health contexts, including chronic disease, 28 winter preparedness, 29 general school health, 30 physical activity, 31 substance abuse, 32 mental illness, 32,33 dietary behaviour change 34,35 and breastfeeding. 36 Digital media have also been evaluated for efficacy in enabling health promoting capacity through processes such as information seeking 37 and holistic self-participatory care.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid development and uptake of new digital media presents significant potential for influencing health behaviours via health education, social marketing and health promotion interventions. New digital media have already been used in a range of health contexts, including chronic disease, 28 winter preparedness, 29 general school health, 30 physical activity, 31 substance abuse, 32 mental illness, 32,33 dietary behaviour change 34,35 and breastfeeding. 36 Digital media have also been evaluated for efficacy in enabling health promoting capacity through processes such as information seeking 37 and holistic self-participatory care.…”
Section: Discussionmentioning
confidence: 99%
“…If it had to be time-limited, young people preferred a 6-week Web-based intervention. Some Web-based interventions for this target group are offered weekly and are generally limited to 8 weeks [ 26 , 27 ]. Survivalkid, in the Netherlands, is unlimited but does not offer structured weekly topics [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are some Web-based interventions specifically designed for this group of young people, including Survivalkid [ 22 , 25 ], Grubbel [ 26 ], and Kopstoring [ 27 ], although more research is needed on the evaluation and suitability of Web-based platforms for this at-risk target group. When developing mental health interventions, it is important to consult with end users [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are some online interventions (mostly from the Netherlands) for young people whose parents have mental illness though these are still in the early stages of development and generally target both adolescent and young adults. These interventions include Survivalkid for 12–25 year olds (49, 50), Grubbel for 15–25 year olds (51) and Kopstoring for 16–25 year olds (52). To date, one randomised controlled trial evaluation has been completed on Kopstoring with positive trends found toward a reduction in internalising symptoms (52).…”
Section: Available Interventions and Service Gapsmentioning
confidence: 99%